Melayani Lansia di Ujung Usia (Studi Tentang Pendampingan Menjelang Kematian Lansia Jawa Di Kalurahan Rejosari Kecamatan Gondangrejo Kabupaten Karanganyar) - Budi Widianto (Yayasan Bina Darma, 2019)
AbstractionThe elderly group who due to physical deterioration and decreased organ function are those close to death. Louis Leahy, described the situation of facing death as a transition from the temporal world to a new life whose concrete form could not be imagined, causing anxiety because it felt snatched from loved ones and loved it and thrown in darkness and silence. This study aims to explain the pattern of assistance before the death of Javanese elderly in the Rejosari sub-district Gondangrejo district Karanganyar district. The study was conducted using qualitative methods. Data collection techniques carried out by in-depth interviews, observation, and study of literature. The research subjects were ten companions who were close to the Javanese elderly at the time of death. Data analysis process includes Data Reduction (data reduction), data display (data presentation) and conclusion drawing (data verification). The results of interviews with these ten people show that in the stages leading up to the death of Javanese elderly according to Elisabeth Kübler-Ross's opinion, they accompanied the elderly from the physical, mental, social and spiritual side. In physical terms, the facilitators provide a special room close to the bathroom, with smooth air circulation and easily available sunlight. Prepare preferred and desired foods, bathe, change clothes, change pampers, check blood sugar levels, blood pressure, cholesterol or gout. Likewise, providing drugs that need to be taken every day. Massaging and applying oil to the diseased part of the body also becomes an inseparable part. In terms of mental mentoring, the mentors condition the atmosphere in which the elderly feel welcome, care for them by often accompanying them, giving encouragement and encouragement so that the elderly do not despair. The companions strengthen the social life of the elderly by inviting friends of the elderly to visit so they do not feel lonely. Shows photos of grandchildren who are out of town holding meetings regularly, making a schedule to accompany the elderly, so that the children and grandchildren take turns accompanying the elderly. The results of interviews obtained in terms of spiritual accompaniment are inviting prayer, reminding human existence in the world, remembering God's promises in the Scriptures and inviting singing spiritual songs, Keywords: Assistance, near death stage, elderly Javanese.